Government Ownership and Dividend Payment Policy - Putri, Pavita Bayu; Yulianto, Arief (Universitas Negeri Semarang, 2020)
The purpose of this study to examine and analyze differences in the average policy of dividend payments with government ownership in companies listed on the Indonesia Stock Exchange in period 2008-2017. Previous research still shows differences in research results or inconsistent results between one study and another. The results showed that the average dividend payment policy carried out by the government was higher than companies that did not have government ownership. This is considered as government ownership, so the amount of dividends distributed will increase. Based on the results of this study it can be concluded that government ownership provides an average higher dividend payment policy than non-government ownership. Suggestions for company management, in making dividend payment policies, the company should always consider the interests of the company’s owners. Investors should pay attention to factors outside the economy in investing. For further researchers, it can be used as an additional reference and research can be done one by one sector.